Terminological potential forming (natural profile) at Ukrainian language lessons on the professional direction (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with some aspects of professional speech forming of future specialists of natural profile by enriching the terminological lexicon. It is focused on text materials and work with words.
Keywords: terminologу; professional speech; principle of tekstotsentrizm; words-terms; terminology with international components